Analysis of Factors Affecting Behavior of the Implementation of Health Protocols to Prevent Corona Virus Disease 2019 (Covid-19) in the Work Area of Ngoro Public Health Center Mojokerto Regency - Sunyoto, Sunyoto; Nurwijayanti, Nurwijayanti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
The community has an important role in breaking the chain of Covid-19 transmission so as not to cause new sources of transmission / clusters in places where people move, interact between people and gather many people. The role of the community in being able to break the chain of Covid-19 transmission (risk of contracting and transmitting) must be carried out by implementing health protocols. This study aims to determine the influence of the factors of knowledge, attitudes, availability of facilities and infrastructure and support for the behavior of implementing health protocols in an effort to prevent Covid-19 in the work area of ​​Ngoro Public Health Center Mojokerto Regency. This research is an analytic survey research with a cross sectional approach. The study population was the population in Ngoro Public Health Center area. The sampling technique used is a simple sampling technique with a total sample size of 348 people. Retrieval of data using a questionnaire. Data analysis using multiple linear regression analysis. The results of this study indicate that the knowledge factor, attitude factor, and support factor partially influence the behavior of implementing health protocols. Attitude factor is the dominant factor affecting the behavior of implementing health protocols. While the knowledge factor, attitude factor, availability of health protocol facilities as well as support factors simultaneously influence the behavior of implementing health protocols in an effort to prevent Covid-19 in the work area of Ngoro Public Health Center Mojokerto Regency. To improve the behavior of implementing health protocols in the community, it is necessary to carry out activities of counseling, education, socialization, dissemination of information and supported by policies and regulations. Examples from health workers and community leaders are also needed in order to become a reference for the community.